The association of serum total bile acid levels with gestational diabetes mellitus: a systematic review and meta-analysis - Mohammadamin Parsaei; Mohadese Dashtkoohi; Mohammad Haddadi; Pegah Rashidian; Zeinab Mansouri; Sedigheh Hantoushzadeh (BMC, 2024)
Abstract Background Given the high prevalence of gestational diabetes mellitus and its significant impact on maternal and neonatal health, identifying reliable biomarkers for prediction and diagnosis is essential. The increased incidence of gestational diabetes mellitus among patients with intrahepatic cholestasis of pregnancy suggests a possible association between serum total bile acid levels and gestational diabetes mellitus. This study evaluated the relationship between total bile acid levels and gestational diabetes mellitus incidence. Methods A systematic search was performed on February 19, 2024, for studies examining the association between total bile acid levels and gestational diabetes mellitus incidence in both the general pregnant population and patients diagnosed with intrahepatic cholestasis of pregnancy. Meta-analyses were conducted to compare pooled total bile acid levels between patients with and without gestational diabetes mellitus, as well as to assess gestational diabetes mellitus prevalence in patients with mild (10 ≤ total bile acid < 40 µmol/L) vs. moderate-to-severe intrahepatic cholestasis of pregnancy (total bile acid ≥ 40 µmol/L). Results 15 observational studies involving 7,238 pregnant women were systematically reviewed. Our meta-analysis found significantly higher serum total bile acid levels in women diagnosed with gestational diabetes mellitus compared to controls in the general population (Hedge's g = 0.29 [0.03,0.54]). However, subgroup analysis indicated that total bile acid levels were only significantly higher in patients measured earlier in pregnancy, before the gestational diabetes mellitus diagnosis, compared to healthy controls (Hedge's g = 0.48 [0.33,0.64]), while no significant difference in total bile acid levels was observed when measurements were taken after the gestational diabetes mellitus diagnosis (Hedge's g = 0.00 [-0.26,0.27]). Additionally, we found that the prevalence of gestational diabetes mellitus was significantly lower in patients with mild intrahepatic cholestasis of pregnancy compared to those with moderate-to-severe intrahepatic cholestasis of pregnancy (Log odds ratio=-0.56 [-0.95,-0.17]). Conclusions This study highlights a complex relationship between serum total bile acid levels and gestational diabetes mellitus incidence, influenced by the timing of measurement. Elevated total bile acid levels early in pregnancy may predict gestational diabetes mellitus, but its diagnostic value may decline later in pregnancy. Trial registration The review protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) on 3/3/2024 under CRD42024516164.